2010
DOI: 10.1002/macp.201000476
|View full text |Cite
|
Sign up to set email alerts
|

Contraction and Collapsing Kinetics of Single Synthetic Polymer Chains at Small Quench Depths

Abstract: Chain contraction and collapsing kinetics of pyrene‐labeled poly(N‐isopropylacrylamide) (PNIPAM) single chains ($\overline {M} _{{\rm n}} $ = 3.64 × 105 g · mol−1, $\overline {M} _{{\rm w}} /\overline {M} _{{\rm n}} $ = 1.17) were investigated by employing the stopped‐flow technique coupled with fluorescence and light scattering detections, which can achieve millisecond jumping of solvent quality from good to above and below the θ‐solvent condition at small quench depths. It was found that the coil‐to‐crumpled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 90 publications
(151 reference statements)
0
6
0
Order By: Relevance
“…Notwithstanding a plethora of publications dealing with the coil‐to‐globule transition in PNIPAM, rather few of them are devoted specifically to its kinetics. Surprisingly, we have not been able to find any publications that would attempt to parameterize the kinetics of the coil‐to‐globule transition in the frameworks of a nucleation model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notwithstanding a plethora of publications dealing with the coil‐to‐globule transition in PNIPAM, rather few of them are devoted specifically to its kinetics. Surprisingly, we have not been able to find any publications that would attempt to parameterize the kinetics of the coil‐to‐globule transition in the frameworks of a nucleation model.…”
Section: Introductionmentioning
confidence: 99%
“…Per this treatment, raising temperature above the binodal (equilibrium) line brings the system into a metastable state that demixes (relaxes) via the process of nucleation, i.e., the formation of tiny droplets of a new phase. The process is relatively slow as it requires overcoming a thermodynamic free-energy barrier associated with the surface energy of the forming droplet.Notwithstanding a plethora of publications dealing with the coil-to-globule transition in PNIPAM, rather few of them [15][16][17][18][19][20][21][22][23][24] are devoted specifi cally to its kinetics. Surprisingly, we have not been able to fi nd any publications that would attempt to parameterize the kinetics of the coil-to-globule transition in the frameworks of a nucleation model.…”
mentioning
confidence: 99%
“…6À18 For example, Liu et al investigated the kinetics of the coil-to-globule transition of a thermally sensitive linear copolymer poly(N-isopropylacrylamide-co-4(1-pyrenyl)butyl acrylate)) (PNIPAM-co-pyrene, M n = 3.64 Â 10 5 g/mol) in water by using a stopped-flow device. 13,14 They found that the chain collapse followed a two-stage kinetics with two characteristic times (τ fast ∼ 12 ms and τ slow ∼ 270 ms). Note that the stopped-flow technique has been widely used to study the kinetics of micellar formation and protein folding with a time resolution of a few milliseconds.…”
Section: ' Introductionmentioning
confidence: 99%
“…The kinetics of the coil-to-globule transition of thermally sensitive polymer has attracted much attention because of its fundamental role in the understanding of the segment–segment and segment–solvent interactions of polymer chains in solutions. The study of the kinetics of collapsing of polymer chains may help us to understand the protein folding and the packing of DNA. Among all the thermally sensitive polymers, poly( N -isopropylacrylamide) (PNIPAM) has been investigated most widely. For example, Liu et al investigated the kinetics of the coil-to-globule transition of a thermally sensitive linear copolymer poly( N -isopropylacrylamide- co -4(1-pyrenyl)butyl acrylate)) (PNIPAM- co -pyrene, M n = 3.64 × 10 5 g/mol) in water by using a stopped-flow device. , They found that the chain collapse followed a two-stage kinetics with two characteristic times (τ fast ∼ 12 ms and τ slow ∼ 270 ms). Note that the stopped-flow technique has been widely used to study the kinetics of micellar formation and protein folding with a time resolution of a few milliseconds.…”
Section: Introductionmentioning
confidence: 99%
“…1–4 Experiments on this transition were carried out using different techniques, such as light scattering, viscometry and NMR. 3,5–19…”
Section: Introductionmentioning
confidence: 99%